2015
DOI: 10.1016/j.mce.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regions in the C-Terminus required for GLP-1R cell surface expression, activity and internalisation

Abstract: The glucagon-like peptide-1 (GLP-1) receptor (GLP-1R), an important drug target in the treatment of type 2 diabetes, is a G-protein coupled receptor (GPCR) that mediates insulin secretion by GLP-1. The N-terminus controls GLP-1R biosynthetic trafficking to the cell surface but the C-terminus involvement in that trafficking is unknown. The aim of this study was to identify distinct regions within the C-terminal domain required for human GLP-1R (hGLP-1R) cell surface expression, activity and internalisation usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…Results are expressed as the mean + standard error of the mean (SEM) of three to five experiments. Statistical significance between multiple groups was determined by the Bonferroni's post hoc test after one-way or two-way analysis of variance (ANOVA), where p <0.05 was considered as statistically significant (Thompson and Kanamarlapudi, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Results are expressed as the mean + standard error of the mean (SEM) of three to five experiments. Statistical significance between multiple groups was determined by the Bonferroni's post hoc test after one-way or two-way analysis of variance (ANOVA), where p <0.05 was considered as statistically significant (Thompson and Kanamarlapudi, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminus has been repeatedly demonstrated to be an indispensable region of GPCRs that govern their cell surface expression (6). In the present study, the effect of C-terminal truncation on the surface expression of OX2R was assessed using an ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…The C-termini of GPCRs differ in terms of their length and structure, implying their functional importance and complexity (5). The C-terminus is indispensable for the functions of GPCRs, including cell surface localization (6), G-protein coupling (7), agonist-driven internalization (8) and signal transduction (9). Therefore, mutations in the C-termini of GPCRs have been associated with a variety of dysfunctions and disease states (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that agonist-induced GLP-1R internalisation is mediated by the Gα q pathway [ 20 ]. In addition, the C-terminus of GLP-1R plays an important role in agonist-induced internalisation of the receptor [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%